Pengaruh Fomo (Fear of Missing Out) Terhadap Impulse Buying pada Suatu Produk Fashion di Marketplace (Tokopedia) - Asyida, Melia Zulfa; Ahmadi, Mirzam Arqy (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Globalization drives the presence of digital markets, including Tokopedia's collaboration with TikTok Shop. This collaboration creates new market opportunities and attractive offers that trigger impulsive buying behavior due to Fear of Missing Out (FoMO). This study aims to analyze the effect of FoMO on impulsive buying of fashion products on Tokopedia. Quantitative methods are used with purposive and convenience sampling techniques, involving 75 respondents. A questionnaire with a Likert Scale was used to collect data, and SmartPLS 3 was used for analysis. The findings show that FoMO has a significant and positive impact on impulsive buying. However, the shortcomings of this study include the small sample size, focus on fashion products, and one platform, so the results cannot be fully generalized. Further research is expected to expand its scope for more comprehensive results.